2021
DOI: 10.3390/nano11071738
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Crystal Growth Characteristics of SnO2 Nanoaggregates Formed by Sequential Low-Temperature Sol-Gel Reaction and Freeze Drying

Abstract: SnO2 nanoparticles are regarded as attractive, functional materials because of their versatile applications. SnO2 nanoaggregates with single-nanometer-scale lumpy surfaces provide opportunities to enhance hetero-material interfacial areas, leading to the performance improvement of materials and devices. For the first time, we demonstrate that SnO2 nanoaggregates with oxygen vacancies can be produced by a simple, low-temperature sol-gel approach combined with freeze-drying. We characterize the initiation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To conclude, we also tried to investigate the recrystallization mechanism of amorphous a -SnO 2 into crystalline SnO 2 , as shown in Figure d,h. We found that by an extra week of annealing at 280 °C, crystalline domains are initially formed on step edges, as shown in Figure d with corresponding interatomic plane distances of 0.33 nm (Figure h), attributed to the (110) plane distances of tetragonal rutile SnO 2 . It turns out that the recrystallization of a -SnO 2 into crystalline SnO 2 proceeds from the outside to the inside of the flake, considering that no nucleating SnO 2 crystallites are visible inside the flakes as shown in Figure d,h.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…To conclude, we also tried to investigate the recrystallization mechanism of amorphous a -SnO 2 into crystalline SnO 2 , as shown in Figure d,h. We found that by an extra week of annealing at 280 °C, crystalline domains are initially formed on step edges, as shown in Figure d with corresponding interatomic plane distances of 0.33 nm (Figure h), attributed to the (110) plane distances of tetragonal rutile SnO 2 . It turns out that the recrystallization of a -SnO 2 into crystalline SnO 2 proceeds from the outside to the inside of the flake, considering that no nucleating SnO 2 crystallites are visible inside the flakes as shown in Figure d,h.…”
Section: Resultsmentioning
confidence: 80%
“…We found that by an extra week of annealing at 280 °C, crystalline domains are initially formed on step edges, as shown in Figure 4 d with corresponding interatomic plane distances of 0.33 nm ( Figure 4 h), attributed to the (110) plane distances of tetragonal rutile SnO 2 . 44 It turns out that the recrystallization of a -SnO 2 into crystalline SnO 2 proceeds from the outside to the inside of the flake, considering that no nucleating SnO 2 crystallites are visible inside the flakes as shown in Figure 4 d,h. The limited extension of the crystalline domains with respect to the amorphous ones shown in Figure 4 d,h may also explain the lack of any diffraction peak attributed to crystalline SnO 2 in the GI-XRD pattern of Figure 3 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hold times at these temperatures were 1 or 6 h. For comparison purposes, one sample was left entirely unsintered. For solar cells, the substrate was sintered at 500 °C as reported previously [ 15 ]. Three substrates for different solar cells (Devices 2–4 as mentioned in the following section) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Both unsintered and sintered substrates were characterized using x -ray diffraction (XRD; Rigaku RINT Ultima/PC with monochromated Cu Kα radiation, Tokyo, Japan). Except for the perovskite layer, the solar cell was assembled using the method that has been previously reported in our group, where TiO 2 substrates were sintered in air at 500 °C [ 15 ]. In regards to the TiO 2 -based electron-transport layer (ETL) in perovskite solar cells, a TiO 2 /FTO substrate was prepared, using the spin-coating process and sintering at 500 °C for comparison (Device 1).…”
Section: Methodsmentioning
confidence: 99%